Enhanced antiviral immunity and dampened inflammation in llama lymph nodes upon MERS-CoV sensing: bridging innate and adaptive cellular immune responses in camelid reservoirs - Rodon, Jordi; Te, Nigeer; Segalés, Joaquim; Vergara-Alert, Júlia; Bensaid, Albert (Frontiers in Immunology, 2023)
Middle East respiratory syndrome coronavirus (MERS-CoV) infection can cause fatal pulmonary inflammatory disease in humans. Contrarily, camelids and bats are the main reservoir hosts, tolerant for MERS-CoV replication without suffering clinical disease. Here, we isolated cervical lymph node (LN) cells from MERS-CoV convalescent llamas and pulsed them with two different viral strains (clades B and C). Viral replication was not supported in LN, but a cellular immune response was mounted. Reminiscent Th1 responses (IFN-γ, IL-2, IL-12) were elicited upon MERS-CoV sensing, accompanied by a marked and transient peak of antiviral responses (type I IFNs, IFN-λ3, ISGs, PRRs and TFs). Importantly, expression of inflammatory cytokines (TNF-α, IL-1β, IL-6, IL-8) or inflammasome components (NLRP3, CASP1, PYCARD) was dampened. The role of IFN-λ3 to counterbalance inflammatory processes and bridge innate and adaptive immune responses in camelid species is discussed. Our findings shed light into key mechanisms on how reservoir species control MERS-CoV in the absence of clinical disease.